Analysis of the Effect of Central Gap Size on the Temperature Profile and Fissile Content in the Annular Nuclear Fuel Rod - Farha, Farhana Islam; Sahadath, Md Hossain (Dhaka University Journal of Applied Science and Engineering, 2022)
The perturbation in temperature profile and fissile content due to variation in the central gap of an isolated annular cylindrical fuel rod of a pressurized water reactor was studied by analytical calculation. Four different models namely UO2+Zircaloy-4+He, UO2+ Zr-1%Nb +He, MOX+Zircaloy-4+He, and MOX+ Zr-1%Nb +He were considered. The radial temperature profile was generated for different ratios (α) of outer to inner fuel radius. Lower fuel temperature was observed for small values of α and vice versa. The peak fuel temperature and temperature drop across the fuel pellets were calculated. Models of MOX fuel showed higher peak fuel temperature and large temperature drop than the models of UO2 for the same fuel cladding. Zr-1%Nb cladding results in a slightly higher fuel temperature than Zircaloy-4 for the same fuel composition. The faster changes of these parameters with α were found for UO2 than MOX fuel. The change in fissile loading with α was also studied and a sharp increase is observed if exceeds α=2.50. DUJASE Vol. 6 (2) 72-76, 2021 (July)